STAGES AND FACTORS AFFECTING THE AUTHORISATION OF JAWI WRITING IN SIX YEARS STUDENTS OF THE SERI DUYONG NATION SCHOOLS OF MALAYSIA - Afriyanto Bin Emri; Ahlam Binti Ibrahim (Universitas Islam Negeri (UIN) Mataram, 2020)
The aim of the study is to identify the extent and level affecting Jawi mastery after the decline in Jawi achievement in Islamic teaching subjects, including the Jawi proficiency test in writing, spelling, multiple-choice questions and Quranic writing. In this context, the main objective of this study is to identify the level of Jawi mastery, the difference between Jawi mastery factor and gender and Jawi mastery factor. The study is a quantitative survey and the selected study sample is a total of 72 students from Sekolah Kebangsaan Seri Duyong Melaka. The research tool is using questionnaires. The data obtained in this quantitative form were analyzed descriptively and side-effects (t-test) to test the null hypothesis (s) of the study. The findings suggest that there is no significant difference in the gender of students with the Jawi mastery factor. Finally, the purpose of this study is to improve the education system with respect to responses at the primary and secondary school levels